FYP examiner allocation system improvement part 2 - Tan, Jun Hao (2018)
The students in School of Computer Science and Engineering are required to complete the module Final Year Project (FYP) to fulfil the requirements of the degree of Bachelor of Computer Science or Computer Engineering. Assessment and examination of the FYPs will have to be done by the faculty staff. This process of examiner allocation is being done by the FYP Examiner Allocation (FEA) system. The current FEA system is built since year 2007 and has become outdated. Several issues exist within the system, therefore an improved current FEA system has been implemented to solve some of these issues. However, there are still several limitations that have not been solved. Therefore, a new FEA system has been developed to solve these limitations and replace the current FEA system. Some key features of the system include user-friendliness, modularity and cross browser compatibility. However, there are also some issues that are yet to be solved. Hence, this project, FYP Examiner Allocation System Improvement Part 2 (SCE17-0221) has been initiated in conjunction with another two projects (SCE17-0220 and SCE17-0222) to solve the remaining issues that exist within the new FEA system.